Pengaruh Iklim Komunikasi Organisasi terhadap Loyalitas Karyawan PT. Familia Indo Sejahtera - Luthfiyah; Adhi Adhi Gurmilang (Ilmu Komunikasi, 2026)
Abstract - This study aims to analyze the influence of organizational communication climate on employee loyalty at PT. Familia Indo Sejahtera, both partially and in terms of the magnitude of the influence (Pace & Faules, 2015; Pandey & Khare, 2012). The method used in this study uses a quantitative approach with an explanatory type (Sugiyono, 2017). The population is 259 employees, with a sample of 73 respondents calculated using the Taro Yamane formula (e = 10%) (Siregar & Siregar, 2013). The purposive sampling technique (Sugiyono, 2016). The online questionnaire instrument with a Likert scale of 1–4 has been tested for validity (r table = 0.230) and reliability (Cronbach's Alpha X = 0.892; Y = 0.788). Data analysis uses Pearson correlation, simple linear regression, and coefficient of determination (Kuncoro, 2013). Pearson correlation = 0.968 (very strong/positive, p <0.01); Regression equation Y = 6.739 + 0.321X; R² = 0.937; t count = 32.539 (p=0.000). Organizational communication climate explains 93.7% of the variance in employee loyalty (Robbins & Judge, 2017). The dimensions of trust, shared decision-making, honesty, downward openness, upward listening, and attention to high-performance goals are crucial in building loyalty (Pace & Faules, 2015). Companies are advised to maintain open communication and communication training for managers. This study fills the gap in studies on organizational communication climate in medium-sized retail companies in Indonesia with high turnover rates.